2008
DOI: 10.1002/mde.1437
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of managerial bonus systems on firm profit and market competition: the cases of pure profit, sales, market share and relative profits compared

Abstract: By designing remuneration schemes based on a bonus rewarding specific firm-level outcomes, the owners|shareholders of a firm can manipulate the behavior of their managers. In practice, different bonus anchors take center stage: some are profit-based, others use sales as the key yardstick and still different ones focus on relative performance vis-�-vis a peer group. In this paper, we focus on the impact of remuneration schemes on firm-level profitability. The profit effect is investigated for (all possible comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
127
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(145 citation statements)
references
References 19 publications
(35 reference statements)
6
127
2
1
Order By: Relevance
“…Moreover, we also follow the standard assumption by managerial delegation theory that the fixed component (salary) of the manager pay is chosen by the firm's owner such that the manager exactly gets his/her opportunity cost, which is normalised to zero. More specifically, following for instance Vickers (1985), Jansen et al (2007Jansen et al ( , 2009), Fanti and Meccheri (2013), Meccheri and Fanti (2014), manager i receives a bonus that is proportional to…”
Section: The Model With Managerial Firmsmentioning
confidence: 99%
“…Moreover, we also follow the standard assumption by managerial delegation theory that the fixed component (salary) of the manager pay is chosen by the firm's owner such that the manager exactly gets his/her opportunity cost, which is normalised to zero. More specifically, following for instance Vickers (1985), Jansen et al (2007Jansen et al ( , 2009), Fanti and Meccheri (2013), Meccheri and Fanti (2014), manager i receives a bonus that is proportional to…”
Section: The Model With Managerial Firmsmentioning
confidence: 99%
“…More precisely, we investigated the situation in which both retailers endogenously choose either a relative profit strategy or a pure profit strategy in the market competition in the fashion of Jansen [6]. Our research proved Jansen's conclusion that firm can make more profits by pursuing relative profit when the rival chase for pure profit maximization.…”
Section: Discussionmentioning
confidence: 69%
“…However, more researches conducted concentrated on competition between private firms. In the context of private oligopoly, Jansen [6] found that a firm using relative performance evaluation would earn more profits when its competitor chases for pure profit. But if two competitors chase for relative profits simultaneously, they may catch in the quagmire of vicious competition as a result [7].…”
Section: Introductionmentioning
confidence: 99%
“…1 Not less important, however, is the understanding of which type of delegation contract would be selected from a menu of di¤erent types. Jansen et al (2009) investigate the strategic choice of managerial incentives in a Cournot industry within the aforementioned threefold menu, and show that, at the subgame perfect equilibrium, owners hire managers through contracts based on comparative performance, the latter being Pareto-e¢ cient for …rms as compared to the two alternatives. Moreover, it turns out that when a …rm delegates while the other does not, the resulting equilibrium outcome at the market stage replicates the Cournot-Stackelberg one, with the managerial …rm leading irrespective of the speci…c nature of the incentive scheme.…”
Section: Introductionmentioning
confidence: 99%